122k views
5 votes
Which expression defines the given series for seven terms? -13 + (-16) + (-19) +...

2 Answers

3 votes


- 13 + ( - 3) = - 16 \\ - 16 + ( - 3) = - 19 \\ - 19 + ( - 3) = - 22 \\ - 22 + ( - 3) = - 25
you have to plus (-3) for each numbers
User Ronny Webers
by
6.1k points
1 vote

Answer:


a_n =-3n-10

Explanation:

-13 + (-16) + (-19) +...

Difference between two terms = -3

-16 -(-13)= -3

-19 -(-16)= -3

Common difference is a constant so it is arithmatic


a_n = a_1+(n-1)d

where 'd' is the difference = -3

a1 is the first term that is -13


a_n = -13+(n-1)(-3)


a_n = -13-3n+3

Combine like terms


a_n =-3n-10

User Deepak Paramesh
by
6.0k points